Teaching Emotions and Descriptive Words Based on Fairy Tales at the Early Stage of Learning - Babajavona, Kamuna Ismailovna (TLEP – International Journal of Multidiscipline, 2025)
This article explores the pedagogical significance of using fairy tales as a means to teach emotions and descriptive vocabulary at the early stage of language learning. The research emphasizes that fairy tales, through their imaginative and emotionally rich narratives, provide young learners with natural contexts for understanding and expressing feelings such as joy, fear, anger, and kindness. By combining linguistic, cognitive, and affective elements, fairy tales enable children to internalize descriptive words like brave, beautiful, sad, and happy through meaningful interaction and storytelling. The study discusses the communicative and emotional advantages of using tales to develop empathy, moral understanding, and intercultural awareness in the classroom. It also highlights the importance of role-play, dramatization, and visual storytelling as effective methods for reinforcing emotional vocabulary. The findings suggest that integrating fairy tales into early language education fosters linguistic competence, emotional literacy, and cultural sensitivity, making the learning process both engaging and developmentally holistic.